Problemy związane z wyceną wartości znaku towarowego - Golej, Robert (Trademark Valuation Problems, 2008)
This article is an attempt to debate some problems connected with estimation of trademarks. The practice of estimation of trademarks, which are identified with value of the brand, is not often wide discussed in domestic literature. The rising significance of legal and non-tangible assets towards creating the value of company induced us to estimate that value. In the article, the most often applied estimation methods of trademarks value and the connected problems are presented. The special attention is paid to the income method.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 189-197